2021
DOI: 10.1039/d1fo00666e
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects ofGrifola frondosathrough the modulation of lipid metabolismviaceramide in mice fed a high-fat diet

Abstract: Obesity is characterized by massive fat deposition and is related to a series of metabolic complications, such as insulin resistance (IR) and steatohepatitis. Grifola frondosa (GF) is a basidiomycete fungus...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…Briefly, liver metabolites mainly affect the composition of gut microbes and the integrity of the intestinal barrier, while gut microbiota regulate the synthesis of bile acids, glucose and lipid metabolism in the liver ( 52 ). Noticeably, many recent studies have shown that functional foods and natural health products, directly or indirectly, prevent obesity and metabolic diseases by improving intestinal diversity ( 25 , 53 ). In the current study, mice fed a HFD exhibited lower diversity and gut microbiota disturbance; however, ATX had a salutary effect on promoting gut microbiota and improving diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, liver metabolites mainly affect the composition of gut microbes and the integrity of the intestinal barrier, while gut microbiota regulate the synthesis of bile acids, glucose and lipid metabolism in the liver ( 52 ). Noticeably, many recent studies have shown that functional foods and natural health products, directly or indirectly, prevent obesity and metabolic diseases by improving intestinal diversity ( 25 , 53 ). In the current study, mice fed a HFD exhibited lower diversity and gut microbiota disturbance; however, ATX had a salutary effect on promoting gut microbiota and improving diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The caecal contents were sent to Shanghai Personal Biotechnology Co., Ltd. to investigate microbial diversity through 16S rRNA analysis on the Illumina MiSeq platform. When the microbial DNA was isolated, PCR of the V3–V4 region of the bacterial 16S rRNA gene was performed using the forward primer 5′-ACTCCTACGGGAGGCAGCA-3′ and the reverse primer 5′-GGACTACHVGGGTWTCTAAT-3′ according to the manufacturer’s protocol ( 24 , 25 ). A previous study illustrated the analytical conditions and detailed parameters ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we choose SV as the positive control drug. According to the doses of G. frondosa usage in our previous study ( 15 ) and the yield of GFPA, the doses of GFPA was finally selected as 50 mg/kg and 100 mg/kg. The NCD-fed (n = 6) mice were intragastrically administered 5 mL/kg normal saline (vehicle-treated NCD-fed mice) for a further 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that Grifola frondosa ( G. frondosa ), which belongs to the Polyporaceae family, regulates lipid metabolism by inhibiting Cer, which further contributes to its anti-obesity effects in mice with diet-induced obesity (DIO) ( 15 ). As one of the main bioactive substances of G. frondosa , crude aqueous polysaccharide extracts have been shown to ameliorate lipid metabolic disorders in HFD-fed rats ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria sequences were uploaded to the NCBI Sequence Read Archive with the accession number PRJNA796779 ( https://www.ncbi.nlm.nih.gov/sra/PRJNA796779 ). This analysis was performed as described in our previous study ( Jiang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%